2022
DOI: 10.1111/aogs.14466
|View full text |Cite
|
Sign up to set email alerts
|

Current practice in the diagnosis and management of fetal growth restriction: An international survey

Abstract: Introduction:The aim of this survey was to evaluate the current practice in respect of diagnosis and management of fetal growth restriction among obstetricians in different countries.Material and methods: An e-questionnaire was sent via REDCap with "click thru" links in emails and newsletters to obstetric practitioners in different countries and settings with different levels of expertise. Clinical scenarios in early and late fetal growth restriction were given, followed by structured questions/response pairin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The two-quartile (FCD 50 ) drop in fetal growth velocity, in conjunction with SGA (< 10 th centile EFW or abdominal circumference) and/or abnormal Doppler, stems from a Delphi consensus definition of FGR 16 , which has since been adopted by ISUOG 17 and FIGO 18 practice guidelines. A recent international survey of obstetricians found that this definition of slow growth was used by over 80% of respondents as a diagnostic criterion for late-onset growth restriction 34 . In the study by MacDonald and colleagues 19 , a > 50 centile drop between 28 and 36 weeks' gestation was observed in only 2.6% of cases, and in our cohort, with an average measurement interval of 3-4 weeks, the incidence was even less (0.7%).…”
Section: Fixed Centile Dropmentioning
confidence: 99%
“…The two-quartile (FCD 50 ) drop in fetal growth velocity, in conjunction with SGA (< 10 th centile EFW or abdominal circumference) and/or abnormal Doppler, stems from a Delphi consensus definition of FGR 16 , which has since been adopted by ISUOG 17 and FIGO 18 practice guidelines. A recent international survey of obstetricians found that this definition of slow growth was used by over 80% of respondents as a diagnostic criterion for late-onset growth restriction 34 . In the study by MacDonald and colleagues 19 , a > 50 centile drop between 28 and 36 weeks' gestation was observed in only 2.6% of cases, and in our cohort, with an average measurement interval of 3-4 weeks, the incidence was even less (0.7%).…”
Section: Fixed Centile Dropmentioning
confidence: 99%
“…Most importantly, intrauterine growth restriction (IUGR) and being small for gestational age (SGA) are two distinct conditions [5][6][7] with different implications for child development. While being born SGA below the tenth percentile may be physiological (e.g., when both parents are small), IUGR indicates a pathophysiology during pregnancy [8]. According to the international Delphi consensus, the diagnosis of IUGR in fetuses below the tenth percentile of estimated fetal weight (EFW) and/or abdominal circumference (AC) should take both decelerating fetal growth trajectories and abnormal Doppler findings into account [7].…”
Section: Introductionmentioning
confidence: 99%
“…While being born SGA below the 10 th percentile may be physiological (e.g., when both parents are small), IUGR indicates a pathophysiology during pregnancy [8]. According to international Delphi consensus, the diagnosis of IUGR in fetuses below the 10 th percentile of estimated fetal weight (EFW) should include both abnormal fetal sizes compared to the respective trajectories and abnormal Doppler findings [7].…”
Section: Introductionmentioning
confidence: 99%